2012
DOI: 10.2495/si120151
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation management of Romaine lettuce in Histosols at two spatial scales: water, energy, leaching and yield impacts

Abstract: Lettuce is an important crop in Canada, mainly grown in South West Quebec muck soils. Lettuce is sensitive to water stress during periods of high crop water requirements, which result in important yields decrease mainly due to tip burn. This physiological disorder can be controlled by adequate irrigation, which is affected by spatial distribution patterns of water needs at different field scales. Such patterns result from spatial variability of soil properties and water drainage, and from evapotranspirative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…5). The results are also consistent with those of Périard et al (2012), who found a significant reduction in tip burn using an irrigation threshold of −15 kPa for the average of three tensiometers at depths of 15, 30, and 45 cm when the ET was >4 mm d −1 . These results also suggest that monitoring at more than one depth provides a better diagnosis of potential stresses because the data showed that water uptake occurs at many depths.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…5). The results are also consistent with those of Périard et al (2012), who found a significant reduction in tip burn using an irrigation threshold of −15 kPa for the average of three tensiometers at depths of 15, 30, and 45 cm when the ET was >4 mm d −1 . These results also suggest that monitoring at more than one depth provides a better diagnosis of potential stresses because the data showed that water uptake occurs at many depths.…”
Section: Resultssupporting
confidence: 91%
“…Histosols on the site were classified as Haplohemists (Soil Survey Staff, 1999). The experimental site was chosen for its high variability of soil water availability and the thickness of its organic soil profile (Lafond et al, 2015; Périard et al, 2012). The thickness of the organic soil profile is closely related to soil water availability calculated throughout the entire rooting depth (Hallema et al, 2015a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water management studies on organic soils have shown that the oxidation is accelerated by excessive drainage, which in turn also increases the rate of biodegradation, reduces the water storage capacity and hydraulic conductivity (Schlotzhauer and Price, 1999), and in some cases causes the organic soil to subside more than a centimeter per year (Shih et al, 1998). Vegetables such as lettuce are very sensitive to water stress during the growth stage when water demand is high and can quickly develop physiological disorders (tip burn) resulting in yield loss (Périard et al, 2012). Understanding the effects of peatland cultivation on soil physical and hydraulic properties is essential for optimizing water management on organic soils, yet there is no quantitative knowledge of the large‐scale effects.…”
mentioning
confidence: 99%
“…Specifically, the objectives were to determine the yield and quality response of these crops to soil water potential irrigation thresholds and to establish links between soil hydraulic properties and the identified thresholds. Numerical models could be successfully used to derive such thresholds (Périard et al, 2013), but simple steady‐state analytical solutions (Yuan and Lu, 2005) requiring few parameters could be easily implemented to achieve such goal. The comparative performances of such analytical solutions have never been evaluated.…”
mentioning
confidence: 99%